RUSIP SEHUBUNGAN PROFIL LIPID DALAM KEADAAN HIPERKOLESTEROLEMIA - Indranila KS; Satrianugraha MD (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Rusip is a fermented fish product made from anchovies. Several lactic acid bacteria have been identified in rusip fermentation. Lacticacid bacteria are known to be able to reduce serum cholesterol. The aim of the research was to know the lipid profile changes due toadministration of rusip in hypercholesterolemia rats. The research was done by using Pre and Post Randomized Controlled Group Design.The research subjects consisted of twenty-eight Sprague Dawley strain white male rats aged 20 weeks with normal body weight, who weregiven a high-fat high-cholesterol diet, then divided into four (4) groups: control group, without Rusip administration; P1, P2 and P3 whoreceived 2.55; 5.10 and 7.65 mg Rusip/g body weight. After 14 days treatment, blood samples were taken to determine the lipid profileusing enzymatic methods. ANOVA or alternative test, was used to test the difference between the groups at the 95% confidence level. Basedon the research, the administration of Rusip in the treatment group caused significant changes in the lipid profiles of hypercholesterolemiarats (p<0.05). The total cholesterol, triglycerides and LDL cholesterol levels decreased significantly in all three treatment doses (p<0.05).The HDL cholesterol increased significantly in all three treatment doses (p<0.05). The highest change in lipid profile results was obtainedin the treatment of P3 to all variables. In this study, it was found that administration of Rusip could improve the state of blood lipidprofiles of hypercholesterolemia rats. Whereas, the highest changes were obtained in treatment with P3.